Rachel Garrison: capstone - Garrison, Rachel, artist (Colorado State University. Libraries, 2023)
The artist's statement: My works are focused on my internal dialogue that is brought to fruition through my imaginative processes. Before starting each piece, I choose a specific concept or experience that I want to explore emotionally. While working with my canvas, I allow my imagination to wander, creating characters and narratives throughout. Being in complete control of this process has been reminiscent of the times when I would play with dolls as a child. My canvas serves as a safe space to engage in the playful and straightforward child-like thought process while coming to terms with complex emotions. Creating in such a way has blessed me with the ability to create hand in hand with my inner child and present self. It has given me the fulfillment of exploring emotions, controlling the narrative, and providing fulfillment for myself. My paintings have become a messy reflection of my entire being and the complexity of life and self. It has given me a window to see myself and how I operate. Artmaking has become an interaction with my adult self, my inner child, and my canvas, all tangled into one conversation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting